Determinan Penerapan Akuntansi Manajemen pada Usaha Mikro Kecil dan Menengah: Bukti Empiris dari Kota Tarakan - Roni Padliansyah; Andre Suandi Simbolon (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2021)
Micro, small and medium enterprises (MSMEs) are one of the economic sectors that absorb the most labor and make a significant contribution to economic growth. One of the most important elements in making decisions in business competition is information about management accounting in an entity. This study aims to determine the factors that influence the use of management accounting in micro, small and medium scale enterprises (MSMEs) in Tarakan City. These factors include: business and production capacity; competitiveness; quality of human resources; business strategy; as well as awareness of business owners / operators of management accounting. This study uses a questionnaire-based survey on a sample of 67 MSMEs in Tarakan. The method used to test the hypothesis is structural equation modeling (SEM) analysis with partial least square (PLS). The results showed that the business and production capacity; and market competition has no effect on the application of management accounting in Tarakan City MSMEs. Even so, there are other variables that show a positive and significant influence on the application of management accounting such as the quality of human resources, business strategy, and owner / operator awareness. The results of this study also provide evidence that the application of management accounting can improve the quality of information obtained by users, facilitate economic decisions, and increase the operational efficiency of MSME entities, especially in Tarakan City.